Development and Use of Biotechnological System Models in Applied Scientific Research - M. A. Kerimov (Сельскохозяйственные машины и технологии)
The paper highlights the difficulties of functioning in multi-parameter systems due to the diverse nature of their link connections. The paper examines a specific case of an «operator-machine-animal» biotechnological system employed in the context of machine milking operations. The system includes three subsystems: two of them have a biological nature and exhibit probabilistic behavior, while the milking machine, serving as a connecting element with inanimate characteristics, is to be regarded as a deterministic technical subsystem. (Research purpose) The research aims to substantiate the conceptual approach to the functioning of an «operator-machine-animal» biotechnical system, taking into account the subsystem interaction patterns. (Materials and methods) The paper explores the conditions governing the operation of biotechnical systems characterized by inherent randomness (in the probabilistic-statistical sense). It was determined that the operation of such a system is influenced by a significantly greater number of factors compared to the «man-machine» system. The biotechnical system as a whole remains stochastic, while its control algorithms maintain a probabilistic nature. The study was conducted by assessing the results obtained through statistical analysis of experimental data, employing methods and techniques of mathematical modeling for technological processes, and exploring key avenues for the development of intelligent digital technologies. (Results and discussion) The utilization of adaptive control principles ensures a high probability of successfully attaining the ultimate objectives. A model for an «operator-machine-animal» system functioning has been developed. The rationale for the efficacy of the interaction between the «machine» and «animal» subsystems is illustrated through the case study of the DeLaval™ DelPro MU480 linear milking machine. A block scheme for the «operator-machine» control system was developed. The performance of the machine milking operator was assessed. A mathematical model detailing the operator's errors was outlined. Criteria for ensuring the operational reliability of the «operator-machine» system were introduced. (Conclusions) The efficiency of a multiply connected biotechnical system is constrained by the zone of maximum adaptation. A mathematical model is provided to describe the functioning of a machine milking operator. The professional stability of an operator, acting as an adaptive and stochastic component, depends on individual attributes and working conditions that need statistical evaluation. The adaptation concept is indicated as a promising area of research. Engineering decisions about the cow milking process are to be based on practical insights into animal ethology, formalized through logical-linguistic models.